Multiple threading of a triple-calix[6]arene host - Iuliano, Veronica; Ciao, Roberta; Vignola, Emanuele; Talotta, Carmen; Iannece, Patrizia; De Rosa, Margherita; Soriente, Annunziata; Gaeta, Carmine; Neri, Placido (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of the triple-calix[6]arene derivative 6 in which three calix[6]arene macrocycles are linked to a central 1,3,5-trimethylbenzene moiety is reported. Derivative 6 is able to give multiple-threading processes in the presence of dialkylammonium axles. The formation of pseudo[2]rotaxane, pseudo[3]rotaxane, and pseudo[4]rotaxane by threading one, two, and three, respectively, calix-wheels of 6 has been studied by 1D and 2D NMR, DOSY, and ESI-FT-ICR MS/MS experiments. The use of a directional alkylbenzylammonium axle led to the stereoselective formation of endo-alkyl pseudo[n]rotaxane stereoisomers.
Keywords: calixarene; multiple-threading; pseudo[n]rotaxane; stereoisomers